2018
DOI: 10.21475/ajcs.18.12.08.pne964
|View full text |Cite
|
Sign up to set email alerts
|

Stability of oil palm (Elaeis guineensis Jacq.) progenies on yield and yield Components across environments using AMMI analysis

Abstract: Southern Thailand is annually affected by climate change, which impacts on yield performance of oil palm. Therefore, effect of climate change on adaptability, cultivation and yield of oil palm in various planting areas was investigated. This research aimed to evaluate the adaptability of six oil palm progenies (cross numbers 110, 118, 119, 130, 132 and 137) at 5 year-old-plants grown in three environmental areas of southern Thailand: Nakhon Si Thammarat, Phatthalung and Songkhla provinces. The experiment was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Okoye et al, (2008) obtuvieron diferencias significativas (p < 0,001) en el genotipo y el periodo de evaluación, para las variables rendimiento de RFF, número de racimos y peso promedio del racimo, en 15 genotipos (Deli x Ténera) evaluados en Nigeria durante 1999-2002. Bueraheng et al, (2018) observaron que las varianzas atribuidas al ambiente, el genotipo y a la interacción GxA, fueron significativas (p < 0,001) para seis progenies E. guineensis Ténera evaluadas en varias localidades del sur de Tailandia, con respecto a la estabilidad del rendimiento de aceite y sus componentes. Según los autores, el rendimiento de cada progenie evaluada depende del ambiente específico en el cual se establece.…”
Section: Discussionunclassified
“…Okoye et al, (2008) obtuvieron diferencias significativas (p < 0,001) en el genotipo y el periodo de evaluación, para las variables rendimiento de RFF, número de racimos y peso promedio del racimo, en 15 genotipos (Deli x Ténera) evaluados en Nigeria durante 1999-2002. Bueraheng et al, (2018) observaron que las varianzas atribuidas al ambiente, el genotipo y a la interacción GxA, fueron significativas (p < 0,001) para seis progenies E. guineensis Ténera evaluadas en varias localidades del sur de Tailandia, con respecto a la estabilidad del rendimiento de aceite y sus componentes. Según los autores, el rendimiento de cada progenie evaluada depende del ambiente específico en el cual se establece.…”
Section: Discussionunclassified
“…The yields are strongly influenced by the environment, which causes varying results, both in several years of planting in one location and in several locations even in different locations in several years of the growing season [18]. Other researchers found that progeny number 110 of oil palm was the most stable among the 6 progenies tested in three different locations [19]. The rainfall data in Kuala Jambi District shows that the rain is not evenly distributed throughout the year.…”
mentioning
confidence: 99%